HYPERTENSION AND DRUG-INDUCED GINGIVAL OVERGROWTH: MECHANISMS, IMPLICATIONS, AND MANAGEMENT STRATEGIES - Bogdan Amărioarei; Diana Tatarciuc; Gabriel Rotundu; Ruxandra Stan; Oana Butnaru; Alexandra Mârțu; Liliana Păsărin; Ionut Luchian (Romanian Journal of Medical and Dental Education)
Hypertension (HTA) is commonly treated with medications that can cause drug-induced gingival overgrowth (DIGO). This study investigates the mechanisms behind DIGO in hypertensive patients, focusing on the effects of calcium channel blockers, immunosuppressants, and anticonvulsants. We explore the cellular and molecular pathways involved, such as collagen synthesis, inflammation, and the role of integrins. Clinical implications include challenges in oral hygiene, periodontal health, and patient quality of life. Management strategies discussed include drug substitution, enhanced oral hygiene, and surgical options. Understanding the link between HTA treatment and gingival overgrowth can help healthcare providers better diagnose and manage this condition, improving patient outcomes and periodontal health.